Development of the Pain Appraisal Inventory: Psychometric Properties - Anita M Unruh; Judith A Ritchie (Pain Research and Management)
OBJECTIVE: To discuss the development, content validity, internal consistency and factor structure of a Pain Appraisal Inventory (PAI).